MicroRNA participates in embryo implantation by modulating endometrial tolerance in sows during peri-implantation period - Li, Wenyuan; Jia, Xinlin; Mao, Xiangyu; Li, Yuanyuan; Wu, De; Xu, Shengyu (Frontiers in Endocrinology, 2025)
MicroRNAs (miRNAs) are a class of non-coding RNA. MiRNAs affect physiological processes by regulating messenger RNA (mRNA) translation of target genes. The peri-implantation period is the period with the most loss of pig embryos, during which the endometrium provides support for embryo selectivity. The effects of miRNAs during the porcine peri-implantation period include roles in pregnancy recognition, embryo adhesion, maternal vascular support, and immune system modulation. 1) During peri-implantation period, miRNAs regulates the synthesis and secretion of estrogen, progesterone and prostaglandin, and thus plays a role in the process of fetal pregnancy recognition and maintenance. 2) miRNAs regulates the expression of integrin, insulin-like growth factor and their receptors in the embryonic adhesion stage, mediates the formation of tight adhesion and invasion of trophoblast cells, and provides structural support for embryonic development. In addition, miRNAs also acted on retinol-binding protein 4, uterine ferritin, cadhrin, matrix metalloproteinase, fibroblast growth factor and other cytokines, creating a suitable environment for embryo growth. 3) A large number of new blood vessels in the endometrium provide sufficient nutrition for the embryo, miRNAs regulates angiogenesis by acting on angiogenic factors and basic fibroblast growth factors and their participating cellular pathways, thus regulating embryo implantation. 4) miRNAs regulates the maternal immune system to prevent the embryo from being rejected by the immune system due to the presence of paternal antigens (swine leukocyte antigen and so on). Here, we reviewed the regulatory role of miRNAs in the peri-implantation period of embryos, in order to provide theoretical support for reducing the loss of embryos during the peri-implantation period by intervening miRNAs expression.